2019
DOI: 10.1108/oir-08-2018-0244
|View full text |Cite
|
Sign up to set email alerts
|

Using social media to explore regional cuisine preferences in China

Abstract: Purpose Food plays an important role in every culture around the world. Recently, cuisine preference analysis has become a popular research topic. However, most of these studies are conducted through questionnaires and interviews, which are highly limited by the time, cost and scope of data collection, especially when facing large-scale survey studies. Some researchers have, therefore, attempted to mine cuisine preferences based on online recipes, while this approach cannot reveal food preference from people’s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 32 publications
0
11
0
1
Order By: Relevance
“…Two document analysis studies collecting people's food review microblogs, found that people living in geographically close areas, rather than climate-close areas, had similar cuisine preferences [46]. They also identified that humidity influenced diet preferences more than temperature [46]. Season, eating ambience, and food appearance also affected participants' food preferences [48].…”
Section: Physical and Social Environmental Factors Influence Food Choicesmentioning
confidence: 99%
See 2 more Smart Citations
“…Two document analysis studies collecting people's food review microblogs, found that people living in geographically close areas, rather than climate-close areas, had similar cuisine preferences [46]. They also identified that humidity influenced diet preferences more than temperature [46]. Season, eating ambience, and food appearance also affected participants' food preferences [48].…”
Section: Physical and Social Environmental Factors Influence Food Choicesmentioning
confidence: 99%
“…Firstly, this review included 17 qualitative studies recruiting immigrants living outside of China, whereas only 8 studies researched Chinese mainlanders. Two studies conducted in China used a document analysis approach which only examined participant food reviews and did not provide a complete picture of food choice determinants [46,48]. A third study (conducted in China and written in Mandarin) was determined to be of poor methodological quality due to its very limited information about participant recruitment, interview methods, and data analysis approach, and did not adequately report the participants' determinants of food choice [33].…”
Section: The Concept Of Tcm Influenced Chinese People's Food Choicementioning
confidence: 99%
See 1 more Smart Citation
“…It is well-known that food preferences vary geographically, both across [12] and within countries [13]. This also applies to visual preferences for food [14], with scholars arguing that if such cultural-related context factors are ignored when developing recommendation systems, biased (and therefore poorer) recommendations will be provided [14]. This makes the relationship between the origin of the food and the individual to whom it should be recommended an important one.…”
Section: Introductionmentioning
confidence: 99%
“…Social media is gaining relevance by being transformed into valuable sources of information and communication, including about food (Zhang et al, 2019). The main reason is that nowadays people tend to share information, pictures or videos of food, recipes or posts from family and friends sharing what they have eaten or will eat (Simeone & Scarpato, 2020).…”
Section: Social Mediamentioning
confidence: 99%